It's a jungle in there : inspiring lessons, hard-won insights, and other acts of entrepreneurial daring - Schussler, Steven; Karlins, Marvin (Union Square Press, 2010)
The founder of the Rainforest Cafe shares the insight of his experience in the entrepreneurial world